Aortic distensibility in bicuspid aortic valve patients with normal aortic diameter. (August 2014) - Moaref, Alireza; Khavanin, Mohammad; Shekarforoush, Shahnaz
Objective: Bicuspid aortic valve (BAV) is associated with aortic abnormalities. The ascending aorta tends to dilate and its elasticity deteriorates. The morphology of the BAV and the elasticity of the proximal ascending aorta seem to influence the outcome. This study aimed to determine the distensibility of the ascending aorta with normal diameter in BAV patients and its relation to its morphology. Methods: This is a cross-sectional study. In the patients with BAV referred for echocardiography, the phenotype was defined as anteroposterior (AP) or mediolateral (ML) leaflet orientations. The aortic distensibility at 5–10 mm above the sinotubular junction was assessed using transthoracic echocardiography in 50 BAV patients, and 50 healthy controls with tricuspid aortic valve (TAV) matched by gender and age. Results: The ascending aorta in BAV patients had less distensibility compared with that in the control subjects (0.00298 ± 0.0023 versus 0.00805 ± 0.0028 cm 2 dynes −1 × 10 −6, respectively, p < 0.001). The ML phenotype of BAVs was more frequent. However, the reduced distensibility was not related to gender and morphology of the valve. Conclusions: Regardless of the valve morphology and also in the absence of aortic dilation, aortic distensibility is impaired in BAV subjects compared with TAV subjects. This finding supports the idea of an intrinsic aortic wall anomalies underlying the impaired elasticity of the aorta in BAV patients.